TREND TAFSIR KONTEMPORER: Komparasi Prosedur Kerja antara Ma’na Cum Maghza dan Tafsīr Maqāṣidī: Komparasi Prosedur Kerja antara Ma’na Cum Maghza dan Tafsīr Maqāṣidī - Ahmad Zaeni (Al-Mufassir: Jurnal Ilmu Alquran, Tafsir dan Studi Islam, 2025)
This article compares the Ma'na Cum Magza approach of Sahiron and the Maqāṣidī Tafsir of Washfi 'Asyur and Abdul Mustaqim. The research methods used are content analysis and comparative methods. The results of the study show that in terms of patterns and technical procedures, both interpretation trends have similarities, but the theory of significance in Ma'na Cum Magza requires a more complex investigation including intertextuality, intratextuality, and macro-historical analysis. Therefore, technically, Ma'na Cum Magza makes it easier to trace the historical context of the revelation of verses, and makes it easier to determine the meaning and meaning that might have been understood by the Prophet Muhammad and his companions. Meanwhile, the investigation of meaning and meaning in Maqāṣidī Tafsir relies more on the analysis of maqāṣid usul al-khamsah (religion, soul, descendants, intellect, and wealth) as in maqāṣid shari'ah. On the other hand, relying on analysis on al-khamsah's proposal prioritizes caution in determining sharia law from verses, for example when it comes to understanding verses that are considered to contain gair ma'qulat al-ma'na according to the agreed interpretation of Islamic scholars. This comparison is just a sample, Tafsir Maqasidi's analysis model has several models other than these three thinkers.